Using bioassays with the green peach aphid (Myzus persicae) to determine residual activity of two systemically soil-applied neonicotinoid insecticides in field-grown tobacco. Issue 4 (2nd October 2017) - Merchán, H. Alejandro; Burrack, Hannah J.
ABSTRACT: Duration of systemic pesticide activity under field conditions has wide implications for pest management. Our aim was to determine the duration of activity of systemic insecticides commonly used in cultivated tobacco ( Nicotiana tabacum ) by measuring the levels of insect infestations on field plots and effects on reproduction and survival of the green peach aphid ( Myzus persicae ) in controlled bioassays using field grown leaves. Plants were treated with different concentrations of two systemic neonicotinoid pesticides, imidacloprid and thiamethoxam, and grown in small field plots. Our results show that these materials are effective under field conditions against aphids for at least 13 weeks after transplant. Pesticides also affected aphid reproduction and nymph survival in bioassays, although some aphids survived on pesticide-treated leaves. We also observed that leaf age affected aphid survival. We showed that neonicotinoids were very effective against M. persicae, aphids are a useful organism to assess pesticide efficacy early in the growing season, but plant characteristics are more important than pesticide concentration in the second half of the growing season.